Direct Effects of Stubble Burning on Some Edaphic Characteristics of Coastal Plain Sands at Different Heating Intensities - Edem, I. D; Okoko, P; Etuk, I. M (Review of Environment and Earth Sciences, 2014)
Stubble burning had been identified as a contributor to soil structural degradation and loss of plant nutrients. Contrary to this, some studies have suggested that burning activities might increase availability of plant nutrients and also reported that charcoal residues and charred biomass left on kiln sites improve the fertility of tropical soils by direct nutrient addition and retention. The effect is not sufficiently understood or quantify in areas with very high rainfall intensity that evidenced in high leaching and erosion associated with slope. We; (1) examined the effect of stubbles burning on soil conditions in acid sands, and (2) identified any changes in soil chemical and physical properties under burning at different level of intensity. The experimental fire was performed with measured dry biomass of 30, 90, 120 kg m-2, in three replicates on the plots to provide three levels of burning and the unburned plots served as control. At each of the sampling points, random spots were core sampled and augered at 0-15 cm depth, with the aid of a Dutch auger and bulked together to give a composite sample. Laboratory methods of analyses were carried out on soil samples for particle size distribution, pH (soil reaction), organic matter contents, total nitrogen, available phosphorus and exchangeable cations (K, Ca, Mg and Na). The textural class of the soils within the study area was found to be sandy loam with sand fraction being the dominant particle size in all locations after burning and was found to have significant effect on the particle size distribution. Coarse sand fraction was higher in the burnt plot with the mean value of 16.00 gkg-1 in 30 and 120 kgm-2, 13.33 gkg-1 in 90 kgm-2 and 12.66 gkg-1 in the unburnt plot. Also soil burnt with 30 and 90 kgm-2 of the dry biomass was found to increase bulk density by 4 and 9 % respectively, while 6 % reduction in bulk density occurred in soil burnt with 120 kgm-2 stubble materials. Total nitrogen content was found to be significantly reduced as a result of burning, while available phosphorus was higher in burnt plots than in the un-burned soil.